The student's activity in university: characterization of students and academic productivity impacts - Maísa Aparecida Oliveira; Maria Cristina Silveira Galan Fernandes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This paper analyzes the profile and the impact of academic productivity in university students' training. The application of questionnaires to 120 undergraduate students from three IFES Sciences centers was carried out and analyzed based on the process of semantic categorization supported by critical perspectives. The data reveal that there is a high index of participation in scientific events and programs for undergraduate research, which confirm the valuation of scientific research. Although this, the social, cultural and political formation of student is deficient, considering the low participation in formal and informal groups, and the low index of traineeship. This fact may indicate a possible expansion of individualism based on competition on campus.